EFFECTIVENESS OF TELEMEDICINEIN HEALTH CARE DELIVERY:A COMPREHENSIVE SYSTEMATIC REVIEW - Mohsen Hassan Hamad Al Murdif, Hamad Masoud Ali Alyami, Mohammed Hadi M Ohamed Almunyif, Hadi Ali Mana, Saud Hassan Hamad Al Murdif , Rashed Ali Mahdi Alyami, Faris Masoud Ali Alyami, Rashed saleh saud almerdaf (Chelonian Research Foundation, 2023)
Introduction: The adoption of telemedicine not only has implications for patient accessibility but also plays a pivotal role in enhancing the efficiency of healthcare delivery systems. The aim of the review is to provide a nuanced understanding of the effectiveness of telemedicine, taking into account not only its proven advantages but also the barriers that warrant careful consideration for sustainable and equitable implementation. Methods:AsystematicsearchstrategyutilizedMedicalSubjectHeadings(MeSH)andfree-textkeywords,employingBoolean operators to refine the search across major databases such as PubMed/MEDLINE, Embase, CINAHL, Cochrane Library, and Scopus. Inclusion criteria prioritized English-language research articles and systematic reviews, focusing on telemedicine interventions' impact on patient outcomes, healthcare accessibility, and system efficiency, with an emphasis on randomized controlled trials (RCTs) and diverse population studies. The two-step screening process, involving independent assessment of titles/abstracts and subsequent full-text review, ensured the inclusion of relevant and high-quality studies, maintaining a systematic and transparent approach to enhance the review's reliability and validity.